Rites of passage for Algonquin & Ojibwe female adolescents: the Berry Fast experience - Wabie, Joey-Lynn (Laurentian University of Sudbury, 2011)
There is a paucity of modern literature available on the Berry Fast experience which is a rite of passage for Algonquin and Ojibwe adolescent girls. This thesis involved Algonquin and Ojibwe adolescent girls who completed their Berry Fast—a rite of passage embarked upon by the adolescent girls with the onset of menarche. The study participants also included the members of a Community Advisory Committee. The adolescent girls who participated in the study have chosen to revive a traditional First Nation rite of passage ceremony by completing the Berry Fast despite the negative societal attitudes that surround menstruation within mainstream society. Assimilation policies have also attempted to absorb the First Nations population into mainstream society, but have not succeeded. Using a modified photovoice method, this researcher sought to elicit answers to four questions regarding spiritual aspects, lived experiences, life changes and the traditional First Nations’ views on moontime (menstruation). The results showed that the Berry Fast strengthened a connection to Mother Earth, Creator, enhanced their understanding of their traditional role as Anishnaabe Kweg (Aboriginal women), and culturally constructed a path upon which they follow. The study also developed a model for informal, traditional knowledge transfer. This thesis further discusses how the academic world, modified research methodologies, and the urban Aboriginal community came together. Master of Social Work